Network performance of integrated UPE with multi-QoS using ethernet service activation test methodology (EtherSAM) ITU-T Y.1564 method for LTE backhaul / Muhamad Abdullah Sangguro - Sangguro, Muhamad Abdullah (2016)
ITU-T Y.1564 is the new standard to replace with obsolete IETF RFC2544 for network performance monitoring. Based on the studies and discussion by Telecommunication Committee in RFC 6815 (2012), Applicability Statement for RFC 2544: Use on Production Networks Considered Harmful. RFC 2544 are not relevant to monitor for LTE network because these RFC is not support for multi-COS monitoring. This paper will evaluate the comparison and performance monitoring for Layer 2 network using Ethernet Service Activation Methodology (EtherSAM) with multi-COS by referring ITU-T Y.1564 method. The measurement tools using Integrated UPE with supported on Layer 2 and Layer 3. The performances were measured base on the Throughput, Jitter, Latency and Frame Loss Measurement. At the end of this paper, prove that by using ITU-T Y.1564 standard is more reliable compared to IETF RFC2544 for LTE backhaul network.